Immersive Haptic Technology to Support English Language Learning Based on Metacognitive Strategies - Adriana Guanuche; Wilman Paucar; William Oñate; Gustavo Caiza (Applied Sciences)
One of the most widely used strategies for learning support is the use of Information and Communication Technologies (ICTs), due to the variety of applications and benefits they provide in the educational field. This article describes the design and implementation of an immersive application supported by Senso gloves and 3D environments for learning English as a second language in Ecuador. The following steps should be considered for the app design: (1) the creation of a classroom with characteristics similar to a real classroom and different buttons to navigate through the scenarios; (2) the creation of a virtual environment where text, images, examples, and audio are added according to the grammatical topic; (3) the creation of a dynamic environment for assessment in which multiple choice questions are interacted with, followed by automatic grading with direct feedback. The results showed that the interaction between the physical and virtual environment through navigation tests with the glove in different 3D environments achieved a complete activation and navigation rate. Teachers showed a clear interest in using the application in their classes as an additional teaching tool to complement the English language teaching process, given that it can increase motivation and memorization in students, as it is an easy-to-use application, and the 3D environments designed are attractive, which would make classes more dynamic. In addition, the availability of the application at any place and time represents a support for the current academic community as it adapts to the needs of today’s world.